2009
DOI: 10.1016/j.jneumeth.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ciliary neurotrophic factor and leukemia inhibiting factor on oxytocin and vasopressin magnocellular neuron survival in rat and mouse hypothalamic organotypic cultures

Abstract: Organotypic cultures of mouse and rat magnocellular neurons (MCNs) in the hypothalamo-neurohypophysial system (HNS) have served as important experimental models for the molecular and physiological study of this neuronal phenotype. However, it has been difficult to maintain significant numbers of the MCNs, particularly vasopressin MCNs, in these cultures for long periods. In this paper, we describe the use of the neurotrophic factors, leukemia inhibiting factor (LIF) and ciliary neurotrophic factor (CNTF) to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…These data are consistent with the observations of Rusnak, et al (2003) who indicated that addition of CNTF to dissociated cultures of magnocellular neurons did not result in increased neuronal survival. However, when CNTF is applied to stationary organotypic cultures of the SON and PVN, survival of axotomized magnocellular neurons is increased significantly (House, et al, 2009, Rusnak, et al, 2002, Rusnak, et al, 2003, Vutskits, et al, 1998, Vutskits, et al, 2003) indicating that CNTF is acting through astrocytes or other glial elements. The precise mechanism(s) by which CNTF influences neuronal survival and axonal sprouting remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with the observations of Rusnak, et al (2003) who indicated that addition of CNTF to dissociated cultures of magnocellular neurons did not result in increased neuronal survival. However, when CNTF is applied to stationary organotypic cultures of the SON and PVN, survival of axotomized magnocellular neurons is increased significantly (House, et al, 2009, Rusnak, et al, 2002, Rusnak, et al, 2003, Vutskits, et al, 1998, Vutskits, et al, 2003) indicating that CNTF is acting through astrocytes or other glial elements. The precise mechanism(s) by which CNTF influences neuronal survival and axonal sprouting remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CNTF signals through the tripartite receptor complex consisting of the specific receptor for CNTF, CNTF receptor alpha (CNTFRα), and the gp130 and LIFRβ receptor subunits, to promote the survival of multiple neuronal phenotypes affected by injury across numerous species (Albrecht, et al, 2002, Arakawa, et al, 1990, Ip, et al, 1991, Larkfors, et al, 1994, Lehwalder, et al, 1989, Magal, et al, 1991, Sendtner, et al, 1990). Moreover, CNTF is a potent promoter of hypothalamic magnocellular neuron survival in vitro (House, et al, 2009, Rusnak, et al, 2002, Rusnak, et al, 2003, Vutskits, et al, 1998, Vutskits, et al, 2003). In our studies we have demonstrated an increase in CNTF-immunoreactivity (Watt, et al, 2006) and CNTFRα mRNA expression (Watt, et al, 2009) within the non-injured contralateral SON, which contains the sprouting and metabolically active magnocellular neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Organotypic cultures were prepared using a modification of techniques described previously (House, et al, 2009, House, et al, 2006, House, et al, 1998, Rusnak, et al, 2002, Rusnak, et al, 2003, Shahar, et al, 2004). Briefly, 6-day-old Sprague Dawley rat pups were decapitated and their brains were removed and placed in chilled Geys Balanced Salt Solution (Gibco, Grand Island, NY) enriched with glucose (5 mg/ml; Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The explants were then incubated for 36 hours at 4°C in highly specific monoclonal mouse antibodies against OT-neurophysin (PS 38, 1:500; a gift from Dr. Harold Gainer) or VP-neurophysin (PS 41, 1:500; a gift from Dr. Harold Gainer). These antibodies were characterized by Ben-Barak et al (1985) and have been consistently utilized to label OT and VP neurons and their processes within organotypic cultures (House, et al, 2009, House, et al, 2006, House, et al, 1998, Rusnak, et al, 2002, Rusnak, et al, 2003, Shahar, et al, 2004, Vutskits, et al, 1998, Vutskits, et al, 2003). Next the cultures were incubated in horse anti-mouse biotinylated secondary antibody (1:500; Vector), followed by avidin-biotin complex (ABC; 10 μl/ml in PBS; Vector ABC Elite kit) for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation